Plan de negocios para la creación de una empresa productora de lácteos en el barrio Chinchil de Villamarin, parroquia Mulaló, cantón Latacunga - Rocha Rocha, Aida Yolanda (2015)
This research has the purpose to determine the economic, physical, human, technological resources for the creation of a dairy company, with this project the development of the company will help in the economy of the neighborhood in ode to improve the income of the inhabitants, through sources working to prevent migration or emigration of young people from this sector and to improve the quality of life of each family, the purpose is take the milk production that exists in neighborhood Chinchil the Villamarin, where it can identify places with more production of the raw material, immediately it cloes an analysis of supply and demand through projection methods in order to check the dissatisfied demand for dairy products from Canton Latacunga, with the market research it can identify different tastes and preferences consumer….